“Mongolophilia” of the political elite in the Tuvan People’s Republic - Otroshchenko, Ivanna V. (The New Research of Tuva, 2020)
The article explores one aspect of the political history of Tuvan People’s Republic, which has not been covered by the researchers yet. The Soviet political discourse often referred to Tuvan politicians as ‘Mongolophilic’, meaning that they were sympathetic to the Mongolian People’s Republic or their commitment to align Tuva and Mongolia. The term was applied by the Soviets only to describe the political sentiments of the Tuvan elites (for instance, referring to the similar moods and orientation of the Buryat-Mongolian political elite and intelligentsia, they used a better-known term ‘pan-Mongolism’). The aim of this article is to demonstrate what exactly the Soviet officials mean by ‘Mongolophilia’; who could be classified as a Mongolophile; what criteria were used for that and if these characteristics were true. The research is based on documents (reports, dispatches, characteristics, correspondence etc.), including those not published and stored in the Russian State Archive of Socio-Political History, f. 495 ‘Executive Committee of the Comintern’ (ECC). Our analysis has shown that the terms ‘Mongolophilia’, ‘Mongolophiles’ and ‘Mongolophilic sentiment’ were used frequently in the Soviet and Comintern discourse of Tuva during the 1920s and the early 1930s. The terms were used most frequently to describe the Khemchik rebellion of 1924. Subsequently, the contacts between Tuvan politicians and Mongolian instructors or the Mongolian consulate in Tuva started to be seen by the Soviet officials as one of the criteria of ‘Mongolophilia’. A major presupposition was that ‘Mongolophilic’ sentiments of Tuvan politicians were based on the desire of allying with the nobility, lamas, feudal lords and all wealthy circles of MPR to contain the revolution in Tuva, and that ideologists of Tuvan “Mongolophilia” all came from among the wealthy Tuvan nobles.